Optimization of ultrasound-assisted aqueous two-phase system extraction of polyphenolic compounds from Aronia melanocarpa pomace by response surface methodology. Issue 3 (16th March 2017) - Xu, Yan-yang; Qiu, Yang; Ren, Hui; Ju, Dong-hu; Jia, Hong-lei
ABSTRACT: Aronia melanocarpa berries are abundant in polyphenolic compounds. After juice production, the pomace of pressed berries still contains a substantial amount of polyphenolic compounds. For efficient utilization of A. melanocarpa berries and the enhancement of polyphenolic compound yields in Aronia melanocarpa pomace (AMP), total phenolics (TP) and total flavonoids (TF) from AMP were extracted, using ultrasound-assisted aqueous two-phase system (UAE-ATPS) extraction method. First, the influences of ammonium sulfate concentration, ethanol–water ratio, ultrasonic time, and ultrasonic power on TP and TF yields were investigated. On this basis, process variables such as ammonium sulfate concentration (0.30–0.35 g mL −1 ), ethanol–water ratio (0.6–0.8), ultrasonic time (40–60 min), and ultrasonic power (175–225 W) were further optimized by implementing Box–Benhnken design with response surface methodology. The experimental results showed that optimal extraction conditions of TP from AMP were as follows: ammonium sulfate concentration of 0.324 g mL −1, ethanol–water ratio of 0.69, ultrasonic time of 52 min, and ultrasonic power of 200 W. Meanwhile, ammonium sulfate concentration of 0.320 g mL −1, ethanol–water ratio of 0.71, ultrasonic time of 50 min, and ultrasonic power of 200 W were determined as optimum extraction conditions of TF in AMP. Experimental validation was performed, where TP and TF yields reached 68.15 ± 1.04 and 11.67 ± 0.63 mg g −1, respectively. Close agreement was found between experimental and predicted values. Overall, the present results demonstrated that ultrasound-assisted aqueous two-phase system extraction method was successfully used to extract total phenolics and flavonoids in A. melanocarpa pomace.